2017
DOI: 10.1116/1.4998920
|View full text |Cite
|
Sign up to set email alerts
|

Influence of N2/H2 and N2 plasma on binary III-nitride films prepared by hollow-cathode plasma-assisted atomic layer deposition

Abstract: The authors reported the hollow-cathode plasma-assisted atomic layer deposition of AlN, GaN, and InN films using N2-only and N2/H2 plasma. In this study, the authors analyzed the effect of plasma gas composition on the properties of deposited binary III-nitride thin films. Toward this goal, AlN, GaN, and InN films were deposited on Si (100) substrates using N2-only (50 sccm), as well as N2/H2 (50 + 50, 50 + 25 sccm) plasma to investigate the impact of H2 flow. Grazing-incidence x-ray diffraction (GIXRD) patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…For poly-GaN ALD (further referred to as GaN ALD), organometallic (e.g., trimethylgallium (TMG) or triethylgallium (TEG)) or halide-based inorganic Ga precursors (e.g., GaCl 3 ) have been used, often utilizing NH 3 or N 2 -H 2 as a nitrogen source. , The challenge of ALD by purely thermal means (i.e., without using additional activation techniques) is the activation of the nitrogen precursor, which is chemically very stable. Thermal ALD of GaN from GaCl 3 and NH 3 has been reported to occur at temperatures exceeding 400 °C. The halide precursor however exhibits several drawbacks, such as difficulty in delivery due to its low vapor pressure (demanding supply- and gas-line heating), etching of the reactor walls from corrosive by-products (e.g., HCl), and Cl incorporation in the growing film .…”
Section: Introductionmentioning
confidence: 99%
“…For poly-GaN ALD (further referred to as GaN ALD), organometallic (e.g., trimethylgallium (TMG) or triethylgallium (TEG)) or halide-based inorganic Ga precursors (e.g., GaCl 3 ) have been used, often utilizing NH 3 or N 2 -H 2 as a nitrogen source. , The challenge of ALD by purely thermal means (i.e., without using additional activation techniques) is the activation of the nitrogen precursor, which is chemically very stable. Thermal ALD of GaN from GaCl 3 and NH 3 has been reported to occur at temperatures exceeding 400 °C. The halide precursor however exhibits several drawbacks, such as difficulty in delivery due to its low vapor pressure (demanding supply- and gas-line heating), etching of the reactor walls from corrosive by-products (e.g., HCl), and Cl incorporation in the growing film .…”
Section: Introductionmentioning
confidence: 99%
“…35,38 The lower BE peak at 396.5 eV is assigned to nitrogen in the form of InN. 23,31,32,[35][36][37][38][39][40][41][43][44][45][46][47][48][49][50][51][52][53] For Ar/N 2 -plasma samples, the additional components are at 397.2 and 398.3 eV. The upper component is preserved aer sputtering into the bulk of the lm and can be assigned to an In-N-O bonding environment, which leaves the middle component unassigned.…”
Section: Resultsmentioning
confidence: 99%
“…33,34 To date, there have been multiple efforts towards low-temperature InN growth via PE-ALD. 17,[30][31][32][35][36][37][38][39][40][41] Initial epitaxial growth of InN at sub-300 C was achieved by plasma-enhanced atomic layer epitaxy (PE-ALE) where the lms exhibited substrate-dependent varying crystallographic orientations. 17,36 In a relatively recent study, PE-ALD of monocrystalline InN lms has also been reported at 250 C using N 2 -plasma on lower-lattice-mismatched ZnO/Al 2 O 3 substrates, where the lms were fully relaxed with no voids or interlayers at the interfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GaN (PE-ALD) [1,8,10,11,13,14,16,20,21,30,35] GaN devices (PE-ALD) [2,4,10,11,17] Nanofibers (PE-ALD) [5,[9][10][11]] Nanostructures (ALD) [18,21] AlGaN (PE-ALD) [1,3] AlN (PE-ALD) [1,5,[19][20][21]29,32] BN (PE-ALD) [5,6,11] InN (PE-ALD) [10,11,15,[19][20][21]33,34] BInN and BGaN (PE-ALD)…”
Section: Materials (And Process) Referencementioning
confidence: 99%